Cannabidiol modulates expression of type I IFN response genes and HIV infection in macrophages - Tomer, Shallu; Mu, Wenli; Suryawanshi, Gajendra; Ng, Hwee; Wang, Li; Wennerberg, Wally; Rezek, Valerie; Martin, Heather; Chen, Irvin; Kitchen, Scott; Zhen, Anjie (Frontiers in Immunology, 2022)
Cannabis (Cannabis sativa) is a widely used drug in the United States and the frequency of cannabis use is particularly high among people living with HIV (PLWH). One key component of cannabis, the non-psychotropic (−)-cannabidiol (CBD) exerts a wide variety of biological actions, including anticonvulsive, analgesic, and anti-inflammatory effects. However, the exact mechanism of action through which CBD affects the immune cell signaling remains poorly understood. Here we report that CBD modulates type I interferon responses in human macrophages. Transcriptomics analysis shows that CBD treatment significantly attenuates cGAS-STING-mediated activation of type I Interferon response genes (ISGs) in monocytic THP-1 cells. We further showed that CBD treatment effectively attenuates 2’3-cGAMP stimulation of ISGs in both THP-1 cells and primary human macrophages. Interestingly, CBD significantly upregulates expression of autophagy receptor p62/SQSTM1. p62 is critical for autophagy-mediated degradation of stimulated STING. We observed that CBD treated THP-1 cells have elevated autophagy activity. Upon 2’3’-cGAMP stimulation, CBD treated cells have rapid downregulation of phosphorylated-STING, leading to attenuated expression of ISGs. The CBD attenuation of ISGs is reduced in autophagy deficient THP-1 cells, suggesting that the effects of CBD on ISGs is partially mediated by autophagy induction. Lastly, CBD decreases ISGs expression upon HIV infection in THP-1 cells and human primary macrophages, leading to increased HIV RNA expression 24 hours after infection. However, long term culture with CBD in infected primary macrophages reduced HIV viral spread, suggesting potential dichotomous roles of CBD in HIV replication. Our study highlights the immune modulatory effects of CBD and the needs for additional studies on its effect on viral infection and inflammation.